Addressing common biases in the evaluation of lifetime alcohol consumption patterns and dementia risk: the EPIC-Spain dementia cohort - Huerta, José M.; Colorado-Yohar, Sandra M.; Andreu-Reinón, M. Encarnación; Mokoroa, Olatz; Tainta, Mikel; Guevara, Marcela; Gasque, Alba; Castilla, Jesús; Petrova, Dafina; Crous-Bou, Marta; Zamora-Ros, Raúl; Sánchez, María José; et al. (Frontiers in Nutrition, 2025)
BackgroundAlcohol consumption has been described to exhibit a J-shaped relationship with dementia risk, but previous observations may be partly biased due to “sick-quitters” and competing risks of death.ObjectiveTo examine the association between baseline and lifetime alcohol consumption and the risk of dementia and subtypes in a large Mediterranean cohort, accounting for lifetime drinking patterns, potential confounding, and competing risks of death.MethodsProspective study of 30,211 participants, 29–69 years at recruitment (1992–1996), from the EPIC-Spain dementia cohort. Alcohol intake was assessed using a validated dietary history and retrospective questionnaires covering ages 20, 30, and 40 years. Dementia cases (n = 1,114) were ascertained through linkage with healthcare and mortality databases and individual medical record review over a mean follow-up of 22.8 years. Multivariate competing risk models were used to estimate sub-hazard ratios (sHRs) for dementia by categories of baseline and lifetime alcohol consumption, using lifetime abstainers as the reference group.ResultsMean lifetime alcohol consumption was 41.9 and 4.4 g/d in men and women, respectively. No significant associations were found between baseline or lifetime alcohol consumption and risk of overall dementia (sHRcurrentvs.never = 0.96, 95% CI: 0.82, 1.13; sHRevervs.never = 0.96, 95% CI: 0.82, 1.11), Alzheimer's disease, or non-Alzheimer subtypes. These null findings remained consistent across strata of sex, BMI or smoking categories, and by beverage type. Sensitivity analyses excluding mis-reporters of energy intake or low-quality diagnoses yielded similar results.ConclusionsIn this large prospective cohort with over 1,100 dementia cases and long-term follow-up, alcohol consumption was not significantly associated with dementia risk. These findings challenge the notion of a protective effect of moderate drinking and warrant continued investigation using methodologically rigorous approaches to clarify the role of alcohol dose, timing, and pattern on dementia risk.